Experimental study on commingled injection in multilayered low-permeability reservoir. Issue 2 (4th March 2017) - Ding, Jingchen
Abstract: Experiments were carried out using natural cores from low-permeability reservoir on three-layer commingled injection system to investigate the recovery characteristics of commingled injection in multilayered low-permeability reservoir. Results indicate that in the cases of commingled injection, ultimate recovery factor of each single layer was always lower than that of single layer injection. Commingled injection has little influence on the high permeability layer, and the influence is much less under stronger heterogeneity/higher injection rate. However, oil recovery of medium/low permeability layer, especially which of low permeability layer, is greatly influenced by reservoir commingled injection, and the influence is greater under stronger heterogeneity/higher injection. And for commingled injection in multilayered low-permeability reservoir, the ultimate recovery percent of low permeability layer is mainly dependent on reservoir heterogeneity instead of permeability.